2024
DOI: 10.3390/s24051647
|View full text |Cite
|
Sign up to set email alerts
|

Visual Detection of Road Cracks for Autonomous Vehicles Based on Deep Learning

Ibrahim Meftah,
Junping Hu,
Mohammed A. Asham
et al.

Abstract: Detecting road cracks is essential for inspecting and assessing the integrity of concrete pavement structures. Traditional image-based methods often require complex preprocessing to extract crack features, making them challenging when dealing with noisy concrete surfaces in diverse real-world scenarios, such as autonomous vehicle road detection. This study introduces an image-based crack detection approach that combines a Random Forest machine learning classifier with a deep convolutional neural network (CNN) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…Experimental results show that SqueezeNet has higher sensitivity in the validation phase. Meftah et al combined a random forest machine learning classifier with MobileNet, InceptionV3, and Xception to construct an efficient CNN model, confirming the model's effectiveness in identifying road cracks on real concrete surfaces [34]. In the detection task, Ma et al used VGG16 as the basic convolutional network to propose a road crack detection method based on a multi-feature layer convolutional neural network, thereby improving the accuracy of road crack identification [35].…”
Section: Model Selectionmentioning
confidence: 97%
“…Experimental results show that SqueezeNet has higher sensitivity in the validation phase. Meftah et al combined a random forest machine learning classifier with MobileNet, InceptionV3, and Xception to construct an efficient CNN model, confirming the model's effectiveness in identifying road cracks on real concrete surfaces [34]. In the detection task, Ma et al used VGG16 as the basic convolutional network to propose a road crack detection method based on a multi-feature layer convolutional neural network, thereby improving the accuracy of road crack identification [35].…”
Section: Model Selectionmentioning
confidence: 97%
“…Ci et al [28] enhanced detection rates by incorporating semantic segmentation and recognition algorithms into a Bayesian framework. Meftah et al [29] achieved an impressive 99.95% accuracy rate using a cuttingedge deep learning model, while Choi et al [30] obtained superior results with rural datasets. Jiang et al [31] suggested an XGBoost-based pedestrian detection method, optimizing the XGBoost model with a genetic algorithm.…”
Section: Introductionmentioning
confidence: 99%